The RANCANG BANGUN SASIS JENIS TANGGA PADA KENDARAAN LISTRIK RODA 3 - Satria, Novian Fajar; Gumilang Samino, Rangga Yoga; Sanggar Dewanto, Raden; Rizani Rusli, Muhammad (MACHINERY Jurnal Teknologi Terapan, 2025)
Several factors that need to be considered in the manufacture of 3-wheeled electric vehicles include vehicle weight, motor selection and control system. These three aspects affect the energy consumption of electric cars. The heavier the vehicle, the greater the energy needed to move it, so that in making a car, the vehicle weight is expected to be not too heavy but also strong and sturdy. This study focuses on discussing the design and construction of the frame on a 3-wheeled electric car. The type of chassis used in 3-wheeled electric vehicles is a ladder chassis type. The research method used is simulation and experimentation of the design and tools that have been made. The material used is 25x25 mm hollow aluminum 6061 with a more efficient design that has a ground clearance of 128 mm. The final result of this study is the total weight of the chassis reaches 20 kg, while the chassis resistance is able to withstand a maximum load of 70 kg.